Synthetic electrospun nanofibers as a supportive matrix in osteogenic differentiation of induced pluripotent stem cells - Matin, Arash Azari; Fattah, Khashayar; Masouleh, Sahand Saeidpour; Tavakoli, Reza; Houshmandkia, Seyed Armin; Moliani, Afshin; Abdolahinia, Elaheh Dalir (Taylor & Francis Ltd, 2022)
Continuous remodeling is not able to repair large bone defects. Bone tissue engineering is aimed to repair these defects by creating bone grafts. To do this, several technologies and biomaterials have been employed to fabricate an in vivo-like supportive matrix. Electrospinning is a versatile technique to fabricate porous matrices with interconnected pores and high surface area, replicating in vivo microenvironment. Electrospun scaffolds have been used in a large number of studies to provide a matrix for bone regeneration and osteogenic differentiation of stem cells such as induced pluripotent stem cells (iPSCs). Electrospinning uses both natural and synthetic polymers, either alone or in combination, to fabricate scaffolds. Among them, synthetic polymers have had a great promise in bone regeneration and repair. They allow the fabrication of biocompatible and biodegradable scaffolds with high mechanical properties, suitable for bone engineering. Furthermore, several attempts have done to increase the osteogenic properties of these scaffolds. This paper reviewed the potential of synthetic electrospun scaffolds in osteogenic differentiation of iPSCs. In addition, the approaches to improve the osteogenic differentiation of these scaffolds are addressed.
Keywords: Electrospinning; induced pluripotent stem cells; osteogenic differentiation; scaffold modification